Oceanic Medicinal Plants as Antidepressants - Wright, Mitchell Henry; Pica II, Derek Anthony (Pharmacognosy Communications)
The Oceanic region is a botanically-rich area comprising four main regions; Australia, Polynesia, Micronesia and Melanesia. Recently, a review was published that describes several region-specific plants significant in the treatment of depression. Traditional medicines are largely overlooked as treatment options for depression, despite being extensively recognized as effective alternatives. In fact, the use of the Polynesian Kava Kava plant is one of the best known and well-documented examples of Oceanic medicinal plants (Cock and Cheesman, 2016). Despite this, most work concentrates on Asian traditional medicines and plants due to their extensive, recorded use over a long period. Nevertheless, Oceanic plants offer great therapeutic alternatives and the authors highlight some major plants specific in the treatment of depression. Though not all-inclusive, the review selects major representative plants and provides backgrounds of each (including colour pictures) as well as chemical structures of compounds relevant as antidepressants. Additionally, the chapter is written in such a way that it is useful for both researchers and clinicians alike. It is logically set out and encompasses sections on plant usage, pharma- cology as well as detailing the phytochemistry of each plant. Overall, it is a fantastic review that combines knowledge of oceanic plants from various sources and highlights the benefit these have as antidepressants.